2021
DOI: 10.1097/shk.0000000000001769
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Drizzle—The Rationale for Abandoning “Cytokine Storm”

Abstract: Background: ''Cytokine storm'' has been used to implicate increased cytokine levels in the pathogenesis of serious clinical conditions. Similarities with Severe Acute Respiratory Syndrome Coronoavirus-2 (SARS CoV-2) and the 2012 Middle Eastern Respiratory Syndrome led early investigators to suspect a ''cytokine storm'' resulting in an unregulated inflammatory response associated with the significant morbidity and mortality induced by SARS CoV-2. The threshold of blood cytokines necessary to qualify as a ''cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…Therefore, the immunologic response develops mainly in the lungs, especially the alveoli, with cytokine concentrations observed in the circulation being only an approximative marker of the intensity of the proinflammatory response [ 24 ]. Numerous studies in patients with disease of varying severity have found consistent values of serum IL-6 levels from 5.0 to approximately 240 pg/mL (see Tables 1 and 2 ), partially depending on the degree of severity [ 11 , 25 , 39 , 42 , 43 , 47 – 58 ]. In mild and moderate COVID-19, requiring hospitalization but not intensive care or resuscitation, circulating IL-6 concentrations are particularly low, around 5 pg/mL [ 42 , 59 ].…”
Section: The Interleukin-6 (Il-6) Pathway and The Inhibition Of Il-6 ...mentioning
confidence: 96%
See 1 more Smart Citation
“…Therefore, the immunologic response develops mainly in the lungs, especially the alveoli, with cytokine concentrations observed in the circulation being only an approximative marker of the intensity of the proinflammatory response [ 24 ]. Numerous studies in patients with disease of varying severity have found consistent values of serum IL-6 levels from 5.0 to approximately 240 pg/mL (see Tables 1 and 2 ), partially depending on the degree of severity [ 11 , 25 , 39 , 42 , 43 , 47 – 58 ]. In mild and moderate COVID-19, requiring hospitalization but not intensive care or resuscitation, circulating IL-6 concentrations are particularly low, around 5 pg/mL [ 42 , 59 ].…”
Section: The Interleukin-6 (Il-6) Pathway and The Inhibition Of Il-6 ...mentioning
confidence: 96%
“…For further information, we recommend that the readers refer to [ 20 23 ]. Among the considerable number of inflammatory mediators produced or secreted in the inflammatory response, interleukin-6 (IL-6) has been shown to play a significant role [ 24 ], which is likely due to its high levels of expression rather than to the singularity of its action, as all mediators produced are somewhat redundant in their actions [ 25 ]. Nonetheless, pro-inflammatory mediators, in particular IL-6, are extensively produced by lung epithelial cells during COVID-19 and notably infect type 2 pneumocytes [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in patients with an unfavorable clinical course, the typical appearance is an exuberant immune response with hyperactivity of dendritic cells, lymphocytes, macrophages, and other immune cells, leading to a self-sustaining and self-amplifying pathophysiology. Usually, elevated levels of inflammatory markers such as IL-6, IL-8, IL-10, ferritin, and CRP are found in these patients; however, CS, sensu stricto, can only be detected in a minority of cases, and some authors claim that “the storm is rather a breeze” [ 134 , 135 , 136 , 137 ]. Yet, primary major compartmentalized CS in the context of COVID-19 occurs regularly in the lungs [ 138 , 139 ].…”
Section: Unleashing the Cytokine Cascadementioning
confidence: 99%
“…The severity of COVID-19 is exacerbated in obese patients in whom a contribution of macrophages, in an activated state in adipose tissue, is suspected 24 . Many scientists have mentioned that a cytokine storm was characteristic of COVID-19, but within the peripheral blood, it is more of a small drizzle 25 - 27 . In contrast, in the most severe patients, this storm operates in their lungs where cytokines contribute to tissue damage and mortality 28 .…”
Section: Compartmentalizationmentioning
confidence: 99%